Utilization of Natural Dyes Substances for Histological Staining: A Review - Hartika, Gita; Zulharmita, Zulharmita; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Histological staining is one the technical processes in the preparation of tissue samples by coloring using histological staining to assist in the study. Natural dyes as an alternative solution to replace synthetic dyes because it can affect human health such as skin allergies, digestive system and respiratory system. This review article aims to determine the quality of natural dyes used to color tissue in the process of making animal and plant tissue preparations. Some of the plants used as natural dyes, coloring indicates a change in tissue preparations. From some plants used for natural dyes in the histology of animal and plant tissues, chemical compounds contained there in that can provide colors such as flavonoids, alkaloids, saponins, tannins, anthocyanins, betasianins, and curcuminoids. The resulting dye looked good or not is influenced by the pH, concentration, staining time, method and solvent used in the staining.